1982
DOI: 10.1111/j.1365-2362.1982.tb02224.x
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics of porcine glucose‐dependent insulinotropic polypeptide (GIP) in man

Abstract: The pharmacokinetics of porcine glucose-dependent insulinotropic polypeptide were investigated in six healthy volunteers. At the maximum infusion dose (0 . 5 pmol kg-1 min-1) a plateau concentration of 115 +/- 5 . 0 pmol/l plasma was obtained. On discontinuation of the infusion, the half-time of disappearance was calculated to be 20 . 3 +/- 1 . 2 min. The metabolic clearance rate was 2 . 6 +/- 0 . 1 ml kg-1 min-1 and the apparent space of distribution was 75 . 8 +/- 5 . 7 ml kg-1. Blood glucose, pancreatic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
4

Year Published

1984
1984
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
2
4
0
4
Order By: Relevance
“…This observation is consistent with previous studies showing that GIP release is not directly related to gastric emptying but is governed by intestinal glucose and fat absorption (Fehmann et al 1995;Schirra et al 1996). In addition, the half-life of GIP in the circulation is remarkably long, approximately 20 min (Sarson et al 1982), and this could well account for the ®nding that in our subjects GIP levels remained elevated throughout the study period.…”
Section: Discussionsupporting
confidence: 93%
“…This observation is consistent with previous studies showing that GIP release is not directly related to gastric emptying but is governed by intestinal glucose and fat absorption (Fehmann et al 1995;Schirra et al 1996). In addition, the half-life of GIP in the circulation is remarkably long, approximately 20 min (Sarson et al 1982), and this could well account for the ®nding that in our subjects GIP levels remained elevated throughout the study period.…”
Section: Discussionsupporting
confidence: 93%
“…The MCR for GIP calculated in the present study using the C-terminal assay is in good agreement with previously reported values using assays of similar specificity (21,22). The MCR for GIP calculated in the present study using the C-terminal assay is in good agreement with previously reported values using assays of similar specificity (21,22).…”
Section: Discussionsupporting
confidence: 91%
“…However, compared to GLP-1, GIP appears to be somewhat less susceptible to DPP IV action, which is a little surprising because in the first nine N-terminal amino acids, the two peptides differ only at positions 1 and 7. Previous studies reported a t 1/2 of approximately 20 min for GIP in man (21,22). In plasma, where DPP IV is probably the only enzyme that contributes significantly to the degradation of both peptides (12), GIP is more stable, with an in vitro t 1/2 about 4 times longer than that of 20 min for GLP-1 (5).…”
Section: Discussionmentioning
confidence: 91%
“…For the same reason, this assay would more accurately measure the rate of GIP secretion than assays directed against biologically active GIP. Compared with GLP-1, the half-life of GIP in the circulation is remarkably long, approximately 20 min (42). However, details about its elimination are not available-for example, whether immunoreactive metabolites (other than possibly GIP 3-41) circulate.…”
Section: Resultsmentioning
confidence: 97%